The Effect of Medical Student Behavior in Personal Listening Devices Usage on The Average of High-Frequency Threshold in Online Learning During Pandemic - Khuznita Dasa Novita; Thareq Barasabha; Diana Evita (Jurnal Ilmu Kedokteran Keluarga, 2023)
During the COVID-19 pandemic, online learning became an unavoidable impact. To adapt, students are increasingly using Personal Listening Devices (PLD) for their online learning needs. However, intensifying and frequent use of PLDs can increase the risk of noise-induced hearing loss, which happens due to noise causing a person's hearing threshold to increase by disrupting the hearing cells in their inner ear's organ of Corti. The objective of this research was to examine whether there exists a correlation between the PLD usage by medical students and their average high-frequency threshold and hearing loss incidence while they study online. A cross-sectional analytic observational design was employed in this study. The dataset was analyzed using Chi-square test. The results showed that the significance value (p value) of the student behavior with hearing threshold average was and hearing loss incidence as follows: the PLD usage (p=0.160, p=0.498); the length of PLD usage (p=0.452, p=0.071); the duration of PLD usage per day before the pandemic (p=0.895, p=0.309); the duration of PLD usage per day during the pandemic (p=0.957, p=0.428); the duration of PLD usage per week before the pandemic (p=0.764, p=0.796); the duration of PLD usage per week during the pandemic (p=0.811, p=0.942); the PLD volume (p=0.731, p=0.731); the time of PLD usage (p=0.812, p=0.092); the increased intensity of PLD usage (p=0.291, p=0.887); the PLD type (p=0.879, p=0.476); and PLD's noise reduction facilities (p=0.879, p=0.353). This study concludes that there is no influence of the PLD usage behavior among the medical students on high-frequency thresholds and hearing loss incidence during pandemic online learning. Abstrak Pada masa COVID-19, pembelajaran daring menjadi salah satu dampak yang tidak bisa dihindari. Salah satu bentuk adaptasi di kalangan mahasiswa adalah peningkatan penggunaan Personal Listening Device (PLD) untuk kebutuhan pembelajaran daring. Peningkatan   intensitas   dan   frekuensi   penggunaan PLD dapat   meningkatkan   risiko terjadinya noise induced hearing loss, yaitu gangguan pendengaran akibat bising dimana terjadi kenaikan ambang dengar seseorang akibat terganggunya sel-sel pendengaran pada organ Corti telinga dalam. Tujuan penelitian ini adalah untuk membuktikan apakah terdapat pengaruh antara perilaku mahasiswa pendidikan dokter dalam menggunakan PLD dengan rata-rata ambang dengar frekuensi tinggi dan angka kejadian gangguan pendengaran selama pembelajaran daring. Metode penelitian yang digunakan adalah desain observasional analitik dengan pendekatan cross sectional. Analisis data dilakukan dengan uji Chi-square. Hasil penelitian menunjukkan bahwa nilai signifikansi antara perilaku mahasiswa dengan rata-rata ambang dengar dan angka kejadian gangguan pendengaran adalah sebagai berikut : pemakaian PLD (p=0.160, p=0.498); lama penggunaan PLD (p=0.452, p=0.071); durasi penggunaan PLD per hari sebelum pandemi (p=0.895, p=0.309); durasi penggunaan PLD per hari saat pandemi (p=0.957, p=0.428); durasi penggunaan PLD per minggu sebelum pandemi (p=0.764, p=0.796); durasi penggunaan PLD per minggu saat pandemi (p=0.811, p=0.942); volume PLD (p=0.731, p=0.731); waktu penggunaan PLD (p=0.812, p=0.092); peningkatan intensitas penggunaan PLD (p=0.291, p=0.887); jenis PLD (p=0.879, p=0.476); dan fasilitas noise reduction pada PLD (p=0,879, p=0.353). Kesimpulan pada penelitian ini adalah perilaku mahasiswa kedokteran dalam memakai PLD tidak berpengaruh terhadap ambang dengar frekuensi tinggi dan angka kejadian gangguan pendengaran selama pembelajaran daring di masa pandemi. Kata Kunci: Perilaku penggunaan PLD, rata-rata ambang dengar frekuensi tinggi, noise induce hearing loss